The minimally important difference in the Rhinoconjunctivitis Total Symptom Score in grass‐pollen‐induced allergic rhinoconjunctivitis. Issue 12 (6th October 2014) - Devillier, P.; Chassany, O.; Vicaut, E.; de Beaumont, O.; Robin, B.; Dreyfus, J. F.; Bousquet, P. J.
Abstract Background The minimally important difference (MID) has been defined as the smallest improvement considered worthwhile by a patient. The MID has not been estimated for the Rhinoconjunctivitis Total Symptom Score (RTSS). Methods In a prospective multicentre study, patients consulting for grass‐pollen‐induced allergic rhinitis (AR) recorded a 15‐point global rating of change scale (GRCS) score and the Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) score on a weekly basis and the individual symptom scores comprising the RTSS on a daily basis over two consecutive weeks. The MID in the RTSS was determined with anchor‐based methods (using the GRCS and the RQLQ) and a distribution‐based method [based on the RTSS' standard deviation (SD)]. Results The study population comprised 806 patients (253 children, 250 adolescents and 303 adults). During the first week of the study, the mean ± SD RTSSs for these age groups were 6.5 ± 3.3, 6.8 ± 3.4 and 7.0 ± 3.4, respectively. For an improvement of 2 points in the GRCS or 0.5 points in the RQLQ score, the regression analysis yielded MIDs in the RTSS of 1.24 ± 0.17 and 1.12 ± 0.14 in children, 1.33 ± 0.14 and 1.20 ± 0.13 in adolescents and 1.13 ± 0.14 and 0.89 ± 0.12 in adults, respectively. When applying distribution‐based methods, the MID ranged from 1.09 to 1.13 (based on 0.33 SDs of the first‐week RTSS) and from 1.22 to 1.40 (based on 0.5 SDs of the difference in RTSSs between the first and second weeks). Conclusion The MID in the RTSS was consistently estimated as 1.1–1.3 (and could conceivably be rounded to 1) in patients with grass‐pollen‐induced AR.